Design and study of a pure tire pyrolysis oil (TPO) and blended with Brazilian diesel using Y-Jet atomizer - Chumpitaz, German R. A.; Coronado, Christian J. R.; Carvalho, João A. [UNESP]; Andrade, José C.; Mendiburu, Andrés Z. [UNESP]; Pinto, Gabriel M.; de Souza, Túlio A. (Springer Nature, 2019)
This manuscript aims to study the atomization and characterization of tire pyrolysis oil (TPO); thus, Y-Jet atomizers have been designed and manufactured by using an experimental bench, which was specifically built for such a purpose. The droplet size was measured experimentally and compared with the theoretical value obtained with the equation proposed by Wigg. The potential for production of TPO in Brazil from tires discarded for 2016 was approximately 190 million liters and in the world for the same year was 4160 million liters; these values represent an excellent alternative for the energetic use of these oils as well as a good way to valorize the by-products obtained from tire pyrolysis such as char and tire gas. The TPO can be used in combustion processes in pure form or mixed with other renewable or non-renewable fuels, so it is important to study atomization processes that guarantee an excellent quality of combustion. The spray quality generated by atomizing pure TPO and in blends (TPO–diesel) has been quantified by droplet size measurement through the Spraytec Malvern 2007 laser diffraction system, whose main properties have also been measured, such as density, viscosity and surface tension of pure liquid fuels and blends, liquid and gas flow pressure at the atomizer nozzle, and droplet size distributions generated by the atomized jet for different gas/liquid ratio values. The influence of the point where liquid pressure exceeds gas pressure at the atomizer nozzle, as well as the TPO percentage effect on droplet size, is demonstrated, and a comparison of experimental droplet size with the one which had been theoretically calculated by Wigg’s equation is made. The study of the atomization of TPO, pure and blends, allows to know a favorable condition for its burning and provides a suitable destination for discarded tires. For a better characterization of the spray, the atomization cone angle was also measured for all the mixtures.
Keywords: Atomization; Compressible fluid; Nozzle; Pyrolysis; Tire